2021
DOI: 10.1016/j.isci.2021.102401
|View full text |Cite
|
Sign up to set email alerts
|

Fire boundaries of lithium-ion cell eruption gases caused by thermal runaway

Abstract: HighlightsWe clarified the three fire boundaries of LIBs corresponding to the fire triangle Batteries are prone to ignition with forced ignition sources Batteries are hard to autoignite when temperatures are low enough LIB ignition modes can be controlled by changing temperatures and ignition sources

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 70 publications
1
20
0
Order By: Relevance
“…), a combustion‐supporting gas (O 2 ), and a high‐temperature environment, it fulfills the ignition triangle necessary for combustion. Hence, breaking through any fire boundary can prevent the ignition of gases, thereby significantly improving the safety performance of the battery 28 …”
Section: Lithium‐ion Batterymentioning
confidence: 99%
“…), a combustion‐supporting gas (O 2 ), and a high‐temperature environment, it fulfills the ignition triangle necessary for combustion. Hence, breaking through any fire boundary can prevent the ignition of gases, thereby significantly improving the safety performance of the battery 28 …”
Section: Lithium‐ion Batterymentioning
confidence: 99%
“…[40] Significantly, interconnected 3D nanochannel-structured materials, including porous carbon, [42,167,172,174,178,[295][296][297] titanium dioxide, [298] cellulose nanofibers, [43] rGO, [129] HGF, [171,299] GO/MXene, [300] cellulose/MXene, [301] and sandwich-like PTCDA/rGO/CNT, [229] are also typically used to develop electrochemical devices. [32,302] For example, Duan et al reported a robust high-performance electrode made of 3D hierarchical porous carbon/metal oxide materials, taking advantage of the accumulation of selective metal ions. [42] The micro/nano channels decorated with metal oxide nanoparticles simultaneously endowed the materials with fast ion transport and mechanical stability.…”
Section:  Energy Storagementioning
confidence: 99%
“…The thermal hazards (such as ignition, internal short circuit, combustion, explosion, toxic gases leakage, and thermal runaway, etc.) caused by high temperatures could lead to the early failure of the LIB cells [22][23][24]. The maximum ∆T is usually set as 5 • C, which is widely elucidated by much relevant research [25][26][27][28][29][30][31].…”
Section: Cooling Performance Indicators and Evaluation Criteriamentioning
confidence: 99%